2019
DOI: 10.33736/jcshd.1922.2019
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence in Malaysian Police: A Review

Abstract: This article discussed the findings of previous studies on emotional intelligence in Royal Malaysia Police. Based on the review, emotional intelligence related to job stress, job satisfaction, job commitment, work-life balance, and psychological well-being of police officers. Review concludes that no significant differences in emotional intelligence by demographic factors like salary, working department, age, marital status, length of service, and job position. Police department has to organise training and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 16 publications
0
26
0
1
Order By: Relevance
“…Another dimension of emotional intelligence is emotional assimilation, described by Kanesan & Fauzan (2019) as the ability to use emotion in facilitating thought processes such as reasoning, problem solving, and interpersonal communication. Within this level, emotions give priority to thinking by focusing attention on important information, and the oscillation of emotional States alters the subject's perspective from optimism to pessimism, leading to the consideration of several points of view.…”
Section: Emotions Personality and Emotional Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…Another dimension of emotional intelligence is emotional assimilation, described by Kanesan & Fauzan (2019) as the ability to use emotion in facilitating thought processes such as reasoning, problem solving, and interpersonal communication. Within this level, emotions give priority to thinking by focusing attention on important information, and the oscillation of emotional States alters the subject's perspective from optimism to pessimism, leading to the consideration of several points of view.…”
Section: Emotions Personality and Emotional Intelligencementioning
confidence: 99%
“…Other intervening abilities are: Interpreting the meaning of emotions in relationships, such as sadness, that sets in because of loss. Understanding complex or simultaneous feelings such as love and hate, or awe as a combination of fear and surprise, as well as recognizing the possible transit from one emotion to another, for example the transition from anger to satisfaction, or from anger to shame (Kanesan & Fauzan, 2019).…”
Section: Emotions Personality and Emotional Intelligencementioning
confidence: 99%
“…We excluded studies that were not published in a peer reviewed journal and/or that did not include an empirical analysis of data. Theoretical, argument and literature review pieces were used for information but were not included in the review (Blumberg et al , 2019; Elfenbein, 2016; Kanesan, 2019; Risan et al , 2016). We also excluded unpublished theses and dissertations (Ezeogu, 2016; Rible, 2012; Smith, 2010), relevant studies that were not published in English (Curbelo et al , 2006; Nascimento and Primi, 2008) and studies for which we could not access the article (Aremu and Tejumola, 2008; Dar et al , 2011; Nathawat and Dadarwal, 2013; Romosiou et al , 2018).…”
Section: Current Studymentioning
confidence: 99%
“…Emotional intelligence indicates an individual skill that accurately perceives and understands one's own emotions (Lee, 2021). It develops a person's ability to detect, understand, express, comprehend, utilise, and regulate emotions in themselves and others (Kanesan, 2019;. Sharing experiences in utilising emotional intelligence skills can lead to team activities, which motivate the workers more creative as they begin to understand and connect the points about the current context and accessible facts (Kaur, 2020).…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Lu et al (2020) indicated that high emotional intelligence has a strong sense of the effects of different emotive tactics; recognising workers' actions and procedures by emotional intelligence may help cross-cultural understandings and minimise conflicts. Moreover, those with high emotional intelligence prefer to emphasise pleasant or good feelings rather than focussing on negative ones (Dasborough, 2019;Kanesan, 2019).…”
Section: Emotional Intelligencementioning
confidence: 99%